Water-based zircon powder coating as well as preparation method and use method thereof
By developing low-viscosity water-based zircon powder coatings, combined with specific proportions and application methods, the problems of existing coatings with high viscosity and poor leveling are solved, and efficient coating establishment and rapid drying are achieved, which significantly improves the The surface quality and anti-sand properties of the castings.
Patent Information
- Application Number
- CN202411358639.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing zircon powder coating has high viscosity, poor leveling properties, inconvenient application, low use efficiency, long drying time, insufficient coating peelability, resulting in poor surface quality of the castings.
Develop a low viscosity water-based zircon powder coating, including refractory aggregates, binders, dispersants, suspensions, wetting agents, defoaming agents and film forming additives, through specific ratios and preparation methods, Improve the density and solid content of the paint, and adopt brush coating combined with spray coating to shorten the drying time.
It improves the efficiency of coating establishment, shortens drying time, enhances anti-sand and peeling properties, and significantly reduces casting defects and after-treatment workload.
Smart Images

Figure BDA0005064341520000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of casting auxiliary materials, and in particular to a water-based zircon powder coating and a preparation method and a use method thereof. Background Art
[0002] In the production of large steel castings, sand cleaning will cost a lot of manpower and material resources, and surface defects of castings are prone to appear during the cleaning process. Reducing the workload of sand cleaning and improving the surface quality of castings has always been a research topic in the foundry industry.
[0003] During the production of castings, coatings can be used to isolate the reaction between molten steel and sand molds to avoid sticking sand. In the production of large steel castings, zircon powder coatings are recognized as coatings that can obtain better casting surfaces, especially when resin sand is used to produce thick and large steel castings, zircon powder coatings have excellent anti-sand sticking effects. However, most zircon powder coatings on the market currently have high viscosity, poor leveling, and are inconvenient to apply. The coating efficiency is low during use, the drying time is long, the coating peelability is insufficient, and the casting surface quality is poor. Summary of the invention
[0004] Based on this, in order to solve the above technical problems, the present invention provides a low-viscosity water-based zircon powder coating and a preparation method and a use method thereof.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A water-based zircon powder coating comprises, by weight, 100 parts of refractory aggregate, 4-10 parts of binder, 2-5 parts of dispersant, 2-8 parts of suspending agent, 0.1-2 parts of wetting agent, 1-4 parts of defoaming agent, 1.5-3 parts of film-forming aid and 10-30 parts of water; the refractory aggregate is zircon powder, including coarse powder and fine powder; the suspending agent comprises component 1 and component 2, component 1 is magnesium silicate; component 2 comprises at least one of sodium bentonite, lithium bentonite and attapulgite; the magnesium silicate is cellulose-modified magnesium silicate.
[0007] Furthermore, the particle size of the coarse powder is below 200 meshes, and the particle size of the fine powder is above 325 meshes; the addition ratio of the coarse powder to the fine powder is 1:0.1-10; and the zirconium oxide content of the zircon powder is ≥65%.
[0008] Furthermore, the dispersant is a polymer dispersant, including at least one of polycarboxylic acid dispersant, sodium polyacrylate, nano inorganic titanium dioxide, and sodium p-styrene sulfonate.
[0009] Furthermore, the binder includes at least one of polyvinyl alcohol, silica sol, and vinyl acetate-ethylene copolymer emulsion.
[0010] Furthermore, the wetting agent includes at least one of HW1000 low foam wetting agent, quaternary ammonium salt, acetylene glycol wetting agent, sodium dodecylbenzene sulfonate, and BYK187.
[0011] Furthermore, the defoaming agent includes at least one of an inorganic silicone defoaming agent, a silicone polyether, bamboo oil, and a water-based latex emulsion.
[0012] Furthermore, the film-forming aid includes at least one of diisobutyl nylonate, alcohol ester dodecanediol, polylactone diol, and ethylene glycol phenyl ether.
[0013] In a second aspect, the present application further provides a preparation method, which is applied to any of the above-mentioned water-based zircon powder coatings, and the preparation method comprises the following steps:
[0014] S110, adding a wetting agent to water and fully dissolving it;
[0015] S120, adding the aqueous solution prepared in step S110 into a dispersion kettle, adding the remaining amount of water, suspending agent and defoaming agent, and dispersing at high speed for 30 minutes to 60 minutes;
[0016] S130, add binder and film-forming aid into the dispersion kettle, and disperse at high speed for 20min to 40min;
[0017] S140, add refractory aggregate and dispersant into the reaction mixture and disperse at high speed for 30min to 50min.
[0018] In a third aspect, the present application also provides a method of use, which is applied to any of the above-mentioned water-based zircon powder coatings, and the water-based zircon powder coating is diluted to 100 to 110 degrees Baume and then applied to the surface of a sand core or sand mold.
[0019] Furthermore, the coating method is a combination of brushing and spraying; that is, a layer of the water-based zircon powder coating is pre-brushed on the sand core or the sand mold's easy-to-stick sand area, and then the sand core or the sand mold is sprayed with 2 or 3 layers of the water-based zircon powder coating as a whole and then dried.
[0020] Compared with the prior art, the method of the present invention has the following beneficial effects:
[0021] The water-based zircon powder coating disclosed in the present invention has low viscosity while maintaining the density and solid content of the coating at a relatively high level, thereby effectively improving the coating establishment efficiency, and the thickness of a single spraying can reach 1.0 to 1.2 mm; the water-based zircon powder coating disclosed in the present invention maintains a relatively high solid content, greatly shortens the coating drying time, and improves the operating efficiency; the water-based zircon powder coating disclosed in the present invention has excellent anti-sand sticking performance and good stripping performance, and is used in the production of castings, especially the production of large steel castings, greatly reducing casting defects and post-processing workload. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] none DETAILED DESCRIPTION
[0023] For ease of understanding of the present invention, the present invention will be described more fully below with reference to relevant embodiments. Preferred embodiments of the present invention are provided in the embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0025] One of the purposes of the present invention is to disclose a water-based zircon powder coating, which comprises, by weight, 100 parts of refractory aggregate, 2-4 parts of binder, 2-5 parts of dispersant, 2-8 parts of suspending agent, 0.1-2 parts of wetting agent, 1-4 parts of defoaming agent, 1.5-3 parts of film-forming aid and 10-30 parts of water. The refractory aggregate is zircon powder, including coarse powder and fine powder; wherein the particle size of the coarse powder is below 200 mesh, and the particle size of the fine powder is above 325 mesh; the addition ratio of the coarse powder to the fine powder is 1:0.1-10. The multi-particle ratio refractory aggregate design effectively increases the solid content and density of the coating; the zircon powder has a zirconium oxide content of ≥65%, has the characteristics of high refractoriness, low expansion rate, strong thermal conductivity, and high thermochemical stability, and effectively reduces the tendency of mechanical and chemical sand adhesion to the surface of the thin-walled sand core. The suspending agent includes component 1 and component 2, wherein component 1 is cellulose-modified magnesium silicate; component 2 includes at least one of sodium bentonite, lithium bentonite, and attapulgite. After magnesium silicate is modified by cellulose, its water solubility is effectively improved; after adding cellulose-modified magnesium silicate to the coating system, the thixotropic property and leveling property of the coating are enhanced, and the fluidity of the coating is significantly improved. The film-forming aid includes at least one of diisobutyl nylonate, alcohol ester dodecahydrate, polylactone diol, and ethylene glycol phenyl ether. In particular, the introduction of diisobutyl nylonate can greatly improve the film-forming property of the coating, and the coating can be quickly established during spraying, thereby improving the efficiency of establishing the coating in a single spraying and increasing the rate of coating thickness formation.
[0026] The binder includes at least one of polyvinyl alcohol, silica sol, and vinyl acetate-ethylene copolymer emulsion; wherein the silica sol is a silane coupling agent modified silica sol (γ-glycidoxypropyltrimethoxysilane (KH-560)), and the silanol groups on the surface of the silica sol particles react with some reactive groups of the silane coupling agent to form covalent bonds, so that the functional groups on the surface of the silica sol particles are no longer single, thereby improving the product performance of the silica sol, and the obtained material has the advantages of both organic and inorganic materials, and has the characteristics of low organic volatiles (VOC) and environmental protection and energy saving.
[0027] A second object of the present invention is to provide a preparation method, which is applied to the water-based zircon powder coating described in any of the above embodiments. The preparation method may include the following steps:
[0028] S110, add 0.1 to 2 parts of wetting agent to 5 to 15 parts of water and fully dissolve;
[0029] S120, adding the aqueous solution prepared in step S110 into a dispersion kettle, adding 5 to 15 parts of water, 2 to 8 parts of suspending agent and 1 to 4 parts of defoaming agent, and dispersing at high speed for 30 minutes to 60 minutes;
[0030] S130, add 4-10 parts of binder and 1.5-3 parts of film-forming aid into the dispersion kettle, and disperse at high speed for 20min-40min;
[0031] S140, add 100 parts of refractory aggregate and 2-5 parts of dispersant into the reaction mixture and disperse at high speed for 30min-50min.
[0032] The third object of the present invention is to provide a method of use, which is applied to any of the above-mentioned water-based zircon powder coatings, and the water-based zircon powder coating is diluted to 100-110 degrees Baume and then applied to the surface of the sand core or sand mold. The application method can be a brushing combined with spraying method, that is, a layer of the water-based zircon powder coating of the present invention is brushed on the sand-adhesive part of the sand core or sand mold in advance, and then the sand core or sand mold is sprayed with 2 or 3 layers of the water-based zircon powder coating of the present invention as a whole, and then dried.
[0033] Embodiment 1
[0034] A water-based zircon powder coating comprises, by weight, 100 parts of refractory aggregate (50 parts of 200-mesh zircon powder and 50 parts of 325-mesh zircon powder), 5 parts of silica sol, 2.4 parts of polycarboxylic acid dispersant, 2.5 parts of sodium bentonite, 2.5 parts of cellulose-modified magnesium silicate, 0.4 parts of sodium dodecylbenzene sulfonate, 0.8 parts of inorganic silicon defoamer, 0.4 parts of bamboo oil, 1.7 parts of diisobutyl nylonate and 20 parts of water.
[0035] The method for preparing the water-based zircon powder coating may include the following steps:
[0036] S110, adding 0.4 parts of sodium dodecylbenzene sulfonate to 10 parts of water, and fully dissolving to prepare an aqueous solution of sodium dodecylbenzene sulfonate;
[0037] S120, adding the sodium dodecylbenzene sulfonate aqueous solution prepared in step S110 into a dispersion kettle, adding another 10 parts of water, 2.5 parts of sodium bentonite, 2.5 parts of cellulose-modified magnesium silicate, 0.8 parts of inorganic silicon defoamer and 0.4 parts of bamboo oil, and dispersing at high speed for 30 minutes to 60 minutes;
[0038] S130, add 5 parts of silica sol and 1.7 parts of diisobutyl nylonate into the dispersion kettle, and disperse at high speed for 20min to 40min;
[0039] S140, add 100 parts of refractory aggregate and 2.4 parts of polycarboxylic acid dispersant into the reaction mixture, and disperse at high speed for 30 minutes to 50 minutes to obtain the water-based zircon powder coating of this embodiment.
[0040] The water-based zircon powder coating of this embodiment is diluted with water to 100-110 degrees Baume, and a layer of the diluted coating is brushed on the sand-adherent parts of the 3D printed sand mold, and then the diluted coating is sprayed 2 or 3 layers on the surface of the 3D printed sand mold using a spraying device. After drying, the surface of each coating is smooth and flat, the coating strength is high, and the thickness of the coating sprayed once is 1.0mm-1.2mm. Each sand mold sprayed with the coating of this embodiment is used to pour the castings. After boxing, there is no sand adhesion defect in the sand-adherent parts of the castings, and the casting surface has a good sand removal effect, excellent stripping performance, and excellent anti-sand adhesion effect.
[0041] Embodiment 2
[0042] A water-based zircon powder coating comprises, by weight, 100 parts of refractory aggregate (40 parts of 200-mesh zircon powder and 60 parts of 325-mesh zircon powder), 6 parts of polyvinyl alcohol, 3 parts of polycarboxylic acid dispersant, 2.5 parts of attapulgite, 2.9 parts of cellulose-modified magnesium silicate, 0.2 parts of sodium dodecylbenzene sulfonate, 0.2 parts of HW1000 low-foam wetting agent, 0.8 parts of inorganic silicon defoamer, 1 part of 1.0 parts of bamboo oil, 0.7 parts of diisobutyl nylonate, 1 part of alcohol ester dodecyl and 16 parts of water.
[0043] The method for preparing the water-based zircon powder coating may include the following steps:
[0044] S110, adding 0.2 parts of sodium dodecylbenzene sulfonate to 4 parts of water and fully dissolving to prepare an aqueous solution of sodium dodecylbenzene sulfonate; adding 0.2 parts of HW1000 low foam wetting agent to 4 parts of water and fully dissolving to prepare an aqueous solution of HW1000 low foam wetting agent;
[0045] S120, adding the sodium dodecylbenzene sulfonate aqueous solution and HW1000 low foam wetting agent aqueous solution prepared in step S110 into a dispersion kettle, adding another 8 parts of water, 2.5 parts of attapulgite, 2.9 parts of cellulose-modified magnesium silicate, 0.8 parts of inorganic silicon defoamer and 1 part of bamboo oil, and dispersing at high speed for 30 minutes to 60 minutes;
[0046] S130, add 6 parts of polyvinyl alcohol, 0.7 parts of diisobutyl nylonate and 1 part of alcohol ester twelve into the dispersion kettle, and disperse at high speed for 20min to 40min;
[0047] S140, add 100 parts of refractory aggregate and 3 parts of polycarboxylic acid dispersant into the reaction mixture, and disperse at high speed for 30 minutes to 50 minutes to obtain the water-based zircon powder coating of this embodiment.
[0048] The water-based zircon powder coating of this embodiment is diluted with water to 100-110 degrees Baume, and a layer of the diluted coating is brushed on the sand-adherent parts of the 3D printed sand mold, and then the diluted coating is sprayed 2 or 3 layers on the surface of the 3D printed sand mold using a spraying device. After drying, the surface of each coating is smooth and flat, the coating strength is high, and the thickness of the coating sprayed once is 1.0mm-1.2mm. Each sand mold sprayed with the coating of this embodiment is used to pour the castings. After boxing, there is no sand adhesion defect in the sand-adherent parts of the castings, and the casting surface has a good sand removal effect, excellent stripping performance, and excellent anti-sand adhesion effect.
[0049] Embodiment 3
[0050] A water-based zircon powder coating comprises, by weight, 100 parts of refractory aggregate (30 parts of 200-mesh zircon powder and 70 parts of 325-mesh zircon powder), 8 parts of vinyl acetate-ethylene copolymer emulsion, 2 parts of polycarboxylic acid dispersant, 1.5 parts of sodium polyacrylate, 2.5 parts of lithium bentonite, 0.5 parts of cellulose-modified magnesium silicate, 0.2 parts of quaternary ammonium salt, 0.6 parts of acetylene glycol wetting agent, 1.6 parts of inorganic silicon defoamer, 0.8 parts of silicone polyether, 0.5 parts of alcohol ester dodecahydrate, 1.8 parts of polylactone diol and 20 parts of water.
[0051] The method for preparing the water-based zircon powder coating may include the following steps:
[0052] S110, adding 0.2 parts of quaternary ammonium salt to 4 parts of water, fully dissolving to prepare a quaternary ammonium salt aqueous solution; adding 0.6 parts of acetylene glycol wetting agent to 5 parts of water, fully dissolving to prepare an acetylene glycol wetting agent aqueous solution;
[0053] S120, adding the quaternary ammonium salt aqueous solution and the acetylene glycol wetting agent aqueous solution prepared in step S110 to a dispersion kettle, adding another 11 parts of water, 2.5 parts of lithium bentonite, 0.5 parts of cellulose-modified magnesium silicate, 1.6 parts of inorganic silicon defoamer, and 0.8 parts of silicone polyether, and dispersing at high speed for 30 minutes to 60 minutes;
[0054] S130, add 8 parts of vinyl acetate-ethylene copolymer emulsion, 0.5 parts of alcohol ester dodecahydrate, and 1.8 parts of polylactone diol into a dispersion kettle, and disperse at high speed for 20 minutes to 40 minutes;
[0055] S140, add 100 parts of refractory aggregate, 2 parts of polycarboxylic acid dispersant, and 1.5 parts of sodium polyacrylate into the reaction mixture, and disperse at high speed for 30 minutes to 50 minutes to obtain the water-based zircon powder coating of this embodiment.
[0056] The water-based zircon powder coating of this embodiment is diluted with water to 100-110 degrees Baume, and a layer of the diluted coating is brushed on the sand-adherent parts of the 3D printed sand mold, and then the diluted coating is sprayed 2 or 3 layers on the surface of the 3D printed sand mold using a spraying device. After drying, the surface of each coating is smooth and flat, the coating strength is high, and the thickness of the coating sprayed once is 1.0mm-1.2mm. Each sand mold sprayed with the coating of this embodiment is used to pour the castings. After boxing, there is no sand adhesion defect in the sand-adherent parts of the castings, and the casting surface has a good sand removal effect, excellent stripping performance, and excellent anti-sand adhesion effect.
[0057] Embodiment 4
[0058] A water-based zircon powder coating comprises, by weight, 100 parts of refractory aggregate (20 parts of 200-mesh zircon powder and 80 parts of 325-mesh zircon powder), 3 parts of polyvinyl alcohol, 3 parts of silane coupling agent-modified silica sol, 4.6 parts of polycarboxylic acid dispersant, 3 parts of sodium bentonite, 3 parts of cellulose-modified magnesium silicate, 0.6 parts of sodium dodecylbenzene sulfonate, 0.8 parts of acetylene glycol wetting agent, 3.2 parts of inorganic silicone defoaming agent, 0.6 parts of bamboo oil, 1.5 parts of nylon acid diisobutyl ester, 0.6 parts of polylactone diol and 25 parts of water.
[0059] The method for preparing the water-based zircon powder coating may include the following steps:
[0060] S110, adding 0.6 parts of sodium dodecylbenzene sulfonate to 5 parts of water, and fully dissolving to prepare an aqueous solution of sodium dodecylbenzene sulfonate; adding 0.8 parts of acetylene glycol wetting agent to 10 parts of water, and fully dissolving to prepare an aqueous solution of acetylene glycol wetting agent;
[0061] S120, adding the sodium dodecylbenzene sulfonate aqueous solution and the acetylene glycol wetting agent aqueous solution prepared in step S110 to a dispersion kettle, adding another 10 parts of water, 3 parts of sodium bentonite, 3 parts of cellulose-modified magnesium silicate, 3.2 parts of inorganic silicon defoamer, and 0.6 parts of bamboo oil, and dispersing at high speed for 30 minutes to 60 minutes;
[0062] S130, add 3 parts of polyvinyl alcohol, 3 parts of silane coupling agent modified silica sol, 1.5 parts of nylon acid diisobutyl ester, and 0.6 parts of polylactone diol into the dispersion kettle, and disperse at high speed for 20min to 40min;
[0063] S140, add 100 parts of refractory aggregate and 4.6 parts of polycarboxylic acid dispersant into the reaction mixture, and disperse at high speed for 30 minutes to 50 minutes to obtain the water-based zircon powder coating of this embodiment.
[0064] The water-based zircon powder coating of this embodiment is diluted with water to 100-110 degrees Baume, and a layer of the diluted coating is brushed on the sand-adherent parts of the 3D printed sand mold, and then the diluted coating is sprayed 2 or 3 layers on the surface of the 3D printed sand mold using a spraying device. After drying, the surface of each coating is smooth and flat, the coating strength is high, and the thickness of the coating sprayed once is 1.0mm-1.2mm. Each sand mold sprayed with the coating of this embodiment is used to pour the castings. After boxing, there is no sand adhesion defect in the sand-adherent parts of the castings, and the casting surface has a good sand removal effect, excellent stripping performance, and excellent anti-sand adhesion effect.
[0065] Embodiment 5
[0066] A water-based zircon powder coating comprises, by weight, 100 parts of refractory aggregate (10 parts of 200-mesh zircon powder and 90 parts of 325-mesh zircon powder), 2 parts of silane coupling agent-modified silica sol, 3 parts of vinyl acetate-ethylene copolymer emulsion, 1.2 parts of nano inorganic titanium dioxide, 3.0 parts of sodium p-styrene sulfonate, 4.0 parts of sodium bentonite, 2.2 parts of cellulose-modified magnesium silicate, 0.2 parts of HW1000 low-foam wetting agent, 0.2 parts of BYK187, 2.5 parts of inorganic silicon defoaming agent, 1.0 parts of bamboo oil, 1.5 parts of alcohol ester dodecahydrate, 2.3 parts of nylon acid diisobutyl ester and 18 parts of water.
[0067] S110, adding 0.2 parts of HW1000 low foam wetting agent to 4 parts of water and fully dissolving to prepare an HW1000 low foam wetting agent aqueous solution; adding 0.2 parts of BYK187 to 4 parts of water and fully dissolving to prepare an BYK187 aqueous solution;
[0068] S120, adding the HW1000 low foam wetting agent aqueous solution and BYK187 aqueous solution prepared in step S110 into a dispersion kettle, adding another 10 parts of water, 4.0 parts of sodium bentonite, 2.2 parts of cellulose modified magnesium silicate, 2.5 parts of inorganic silicon defoamer, and 1.0 part of bamboo oil, and dispersing at high speed for 30min to 60min;
[0069] S130, add 2 parts of silane coupling agent modified silica sol, 3 parts of vinyl acetate-ethylene copolymer emulsion, 1.5 parts of alcohol ester dodecahydrate, and 2.3 parts of nylon acid diisobutyl ester into the dispersion kettle, and disperse at high speed for 20min to 40min;
[0070] S140, add 100 parts of refractory aggregate, 1.2 parts of nano inorganic titanium dioxide, and 3.0 parts of sodium p-styrene sulfonate into the reaction mixture, and disperse at high speed for 30 minutes to 50 minutes to obtain the water-based zircon powder coating of this embodiment.
[0071] The water-based zircon powder coating of this embodiment is diluted with water to 100-110 degrees Baume, and a layer of the diluted coating is brushed on the sand-adherent parts of the 3D printed sand mold, and then the diluted coating is sprayed 2 or 3 layers on the surface of the 3D printed sand mold using a spraying device. After drying, the surface of each coating is smooth and flat, the coating strength is high, and the thickness of the coating sprayed once is 1.0mm-1.2mm. Each sand mold sprayed with the coating of this embodiment is used to pour the castings. After boxing, there is no sand adhesion defect in the sand-adherent parts of the castings, and the casting surface has a good sand removal effect, excellent stripping performance, and excellent anti-sand adhesion effect.
[0072] In order to further demonstrate the excellent performance of the water-based zircon powder coatings of various embodiments of the present invention, conventional water-based zircon powder coatings are used as comparative examples to verify the excellent performance of the water-based zircon powder coatings of various embodiments of the present invention. The specific experimental results are shown in Table 1:
[0073] Table 1 Experimental results
[0074]
[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A water-based zircon powder coating, characterized in that: In parts by weight, it comprises: 100 parts of refractory aggregate, 4 to 10 parts of binder, 2 to 5 parts of dispersant, 2 to 8 parts of suspending agent, 0.1 to 2 parts of wetting agent, 1 to 4 parts of defoaming agent, 1.5 to 3 parts of film-forming aid and 10 to 30 parts of water; The refractory aggregate is zircon powder, including coarse powder and fine powder; The suspending agent comprises component 1 and component 2, wherein component 1 is magnesium silicate; and component 2 comprises at least one of sodium bentonite, lithium bentonite and attapulgite; The magnesium silicate is cellulose-modified magnesium silicate.
2. The water-based zircon powder coating according to claim 1, characterized in that: The particle size of the coarse powder is below 200 meshes, and the particle size of the fine particles is above 325 meshes; the addition ratio of the coarse powder to the fine particles is 1:0.1-10.
3. The water-based zircon powder coating according to claim 1, characterized in that: The dispersant is a polymer dispersant, including at least one of polycarboxylic acid dispersant, sodium polyacrylate, nano inorganic titanium dioxide, and sodium p-styrene sulfonate.
4. The water-based zircon powder coating according to claim 1, characterized in that: The binder includes at least one of polyvinyl alcohol, silica sol, and vinyl acetate-ethylene copolymer emulsion.
5. The water-based zircon powder coating according to claim 1, characterized in that: The wetting agent includes at least one of HW1000 low foam wetting agent, quaternary ammonium salt, acetylene glycol wetting agent, sodium dodecylbenzene sulfonate, and BYK187.
6. The water-based zircon powder coating according to claim 1, characterized in that: The defoamer comprises at least one of an inorganic silicon defoamer, an organic silicon polyether, bamboo oil, and an aqueous latex emulsion.
7. The water-based zircon powder coating according to claim 1, characterized in that: The film-forming aid includes at least one of diisobutyl nylonate, alcohol ester dodecanedioic acid, polylactone diol, and ethylene glycol phenyl ether.
8. A preparation method, applied to the water-based zircon powder coating according to any one of claims 1 to 7, characterized in that: The steps include: S110, adding a wetting agent to water and fully dissolving it; S120, adding the aqueous solution prepared in step S110 into a dispersion kettle, adding the remaining amount of water, suspending agent and defoaming agent, and dispersing at high speed for 30 minutes to 60 minutes; S130, add binder and film-forming aid into the dispersion kettle, and disperse at high speed for 20min to 40min; S140, add refractory aggregate and dispersant into the reaction mixture and disperse at high speed for 30min to 50min.
9. A method of use, applied to the water-based zircon powder coating according to any one of claims 1 to 7, characterized in that: The water-based zircon powder coating is diluted to 100-110 degrees Baume and then applied to the surface of the sand core or sand mold.
10. The method of use according to claim 9, characterized in that: The coating method is a combination of brushing and spraying; A layer of the water-based zircon powder coating is pre-brushed on the sand core or the sand mold's sand-adhesive parts, and then 2 or 3 layers of the water-based zircon powder coating are sprayed on the entire sand core or the sand mold, followed by drying.
Citation Information
Patent Citations
Casting coating for coated sand mold and preparing method of casting coating
CN107414016A
3D printing sand core cast aluminum water-based paint and preparation method thereof
CN116652103A
Anti-burnt-on sand water-based casting coating and preparation method thereof
CN117798320A
Cited By
Water-based anti-veining coating composition for casting industry
CN117123731A
A water-based anti-wrinkle coating composition for the foundry industry
CN117123731B
